Design and Build Attendance Interface System Using RFID-PC - Sibarani, Rudi; Turnip, Marganda (Marcha Institute, 2024)
Attendance is a routine before carrying out activities such as education at schools and campuses. This is a list of attendance records present when starting the activity until the activity ends. At this time the attendance system used is still manual by hand. In this case the attendance system will be created automatically using an RFID tag as an identification card and an RFID reader as a card reader. This tool works by using two series contained in the AT89S52 microcontroller as an RFID Starter Kit controller. Communication uses serial communication or RS 232. Communication with the microcontroller used in the RFID Starter Kit is serial while RS 232 is used in the microcontroller module. In addition to the addition of hardware, this tool is supported by design software including Visual Basic 6 and SQL. Visual Basic is used for programming student data processing and SQL is used for student databases. The advantage of this tool is that it is relatively inexpensive and does not require a computer. So there are only tools present in each class to replace the PC and on the server side there is a PC as the center